2023
DOI: 10.1111/febs.16736
|View full text |Cite
|
Sign up to set email alerts
|

Efficient polyethylene terephthalate degradation at moderate temperature: a protein engineering study of LC‐cutinase highlights the key role of residue 243

Abstract: Enzymatic degradation of poly(ethylene terephthalate) (PET) is becoming a reality because of the identification of novel PET‐hydrolysing enzymes (PHEs) and the engineering of evolved enzyme variants. Here, improved variants of leaf‐branch compost cutinase (LCC), a thermostable enzyme isolated by a metagenomic approach, were generated by a semi‐rational protein engineering approach. Starting from a deleted LCC form lacking the secretion signal (ΔLCC), single and double variants possessing a higher activity on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Second, we used copper-catalyzed azide-alkyne cycloaddition (CuAAC) to functionalize the −N 3 groups with an aromatic ester-containing biotin probe. We hypothesized that the aromatic ester-containing probe would serve as a better mimic of PET than previously employed nitro-phenolate-based probes, the hydrolysis of which correlates poorly with activity for PET plastic degradation . Highly active surface-displayed enzymes cleave the proximal aromatic ester chains, releasing biotin from the yeast surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we used copper-catalyzed azide-alkyne cycloaddition (CuAAC) to functionalize the −N 3 groups with an aromatic ester-containing biotin probe. We hypothesized that the aromatic ester-containing probe would serve as a better mimic of PET than previously employed nitro-phenolate-based probes, the hydrolysis of which correlates poorly with activity for PET plastic degradation . Highly active surface-displayed enzymes cleave the proximal aromatic ester chains, releasing biotin from the yeast surface.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts to further improve the thermostability of LCC-ICCG have resulted in variants such as ICCG_RIP and ICCG_I6M. , These respective efforts employed rational design focused on improving internal hydrophobic interactions or machine learning to predict residues influencing thermostability. In another example, in silico site-saturation mutagenesis was used to identify a double mutant of wild-type LCC with improved activity . The PET-depolymerization activity of Is PETase has also been improved through directed evolution, resulting in engineered variants such as HotPETase, FAST-PETase, and DuraPETase. These variants exhibit greatly improved thermostability and PET-depolymerization kinetics relative to Is PETase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, enzymatic incubation above 70 °C does not permit complete degradation of the amorphized PET due to an ageing process that results into polymer recrystallization after <10 h [ 139 , 140 ]. Recent studies [ 140 , 141 , 142 ] revealed relatively high degradation rates, even when performing the reaction at lower temperatures (50 to 60 °C), despite requiring more time (≥1 day). These milder conditions were also tested on untreated and non-micronized low-crystallinity post-consumer PET materials [ 92 , 93 ].…”
Section: Biotechnological Systems Applied To Plastic Depolymerization...mentioning
confidence: 99%
“…[ 205 ] Whereas, a novel S101N/F243T ΔLCC variant of PET‐hydrolyzing enzyme was found to depolymerize 1.3 g of PET waste in less than 3 days at 55 °C. [ 206 ] Although, the current plastic lifecycle is far from circular economy; an estimate by Ellen Macarthur foundation projected that with ideal application of circular economy has the potential to reduce the annual incorporation of plastic wastes into the sea by 80%. Lack of such projections in the bioenzymatic degradation of plastic makes it difficult to ascertain any superiority among the circular economy and bioenzymatic degradation approach of plastic waste management.…”
Section: Economic Impact and Sustainable Implications Of Protein‐pnp ...mentioning
confidence: 99%